Aolatg1 and Aolatg13 Regulate Autophagy and Play Different Roles in Conidiation, Trap Formation, and Pathogenicity in the Nematode-Trapping Fungus Arthrobotrys oligospora - Zhou, Duanxu; Zhu, Yingmei; Bai, Na; Xie, Meihua; Zhang, Ke-Qin; Yang, Jinkui (Frontiers in Cellular and Infection Microbiology, 2022)
Autophagy is a conserved cellular recycling and trafficking pathway in eukaryotes that plays an important role in cell growth, development, and pathogenicity. Atg1 and Atg13 form the Atg1–Atg13 complex, which is essential for autophagy in yeast. Here, we characterized the roles of the Aolatg1 and Aolatg13 genes encoding these autophagy-related proteins in the nematode-trapping fungus Arthrobotrys oligospora. Investigation of the autophagy process by using the AoAtg8-GFP fusion protein showed that autophagosomes accumulated inside vacuoles in the wild-type (WT) A. oligospora strain, whereas in the two mutant strains with deletions of Aolatg1 or Aolatg13, GFP signals were observed outside vacuoles. Similar results were observed by using transmission electron microscopy. Furthermore, deletion of Aolatg1 caused severe defects in mycelial growth, conidiation, conidial germination, trap formation, and nematode predation. In addition, transcripts of several sporulation-related genes were significantly downregulated in the ΔAolatg1 mutant. In contrast, except for the altered resistance to several chemical stressors, no obvious differences were observed in phenotypic traits between the WT and ΔAolatg13 mutant strains. The gene ontology analysis of the transcription profiles of the WT and ΔAolatg1 mutant strains showed that the set of differentially expressed genes was highly enriched in genes relevant to membrane and cellular components. The Kyoto Encyclopedia of Genes and Genomes analysis indicated that differentially expressed genes were highly enriched in those related to metabolic pathways, autophagy and autophagy-related processes, including ubiquitin-mediated proteolysis and SNARE interaction in vesicular transport, which were enriched during trap formation. These results indicate that Aolatg1 and Aolatg13 play crucial roles in the autophagy process in A. oligospora. Aolatg1 is also involved in the regulation of asexual growth, trap formation, and pathogenicity. Our results highlight the importance of Aolatg1 in the growth and development of A. oligospora, and provide a basis for elucidating the role of autophagy in the trap formation and pathogenicity of nematode-trapping fungi.